Strategic Decision-Making and Firm Performance in Business Ecosystem: A Systematic Literature Review - Hamonangan, Mahardhika Michael; Purwana, Dedi; Mukhtar, Saparuddin; Wahono, Puji (AGUSPATI Research Institute, 2024)
This study conducts a systematic literature review to examine the correlation between strategic decision-making and the performance of firms within business ecosystems. The study seeks to investigate three specific research inquiries: the recent research worked on the subject, recent patterns on this research, and the theoretical and practical consequences of strategic decision-making and the firms performance within the business ecosystems. By employing an eight-step systematic literature review methodology, we conducted an analysis of 398 papers, which finally selecting and examining five pivotal studies that satisfied the inclusion criteria. The findings underscore the small yet expanding research in this field, underscoring the significance of inventive and data-oriented approaches in improving company performance. The assessment emphasizes the necessity of conducting additional research in order to create comprehensive performance metrics that are specifically designed for collaborative business ecosystems.